ALIH FUNGSI LAHAN DI PERKOTAAN (STUDI KASUS DI KOTA BANDUNG DAN YOGYAKARTA) - Prihatin, Rohani Budi (Pusat Analisis Keparlemenan Badan Keahlian Sekretariat Jenderal DPR RI, 2015)
Over the past four decades the cities and towns of Indonesia have experienced dramatic population growth. Population growth makes crisis in land use and agriculture that could undermine the health, security, and sustainability of those cities. The purpose of this study is to determine the land use patterns and its changes over time in Bandung City and Yogyakarta City. The research has been done in 2014, by using qualitative method. By considering urbanization and demographic aspect, this study concludes that decision maker in those cities are inconsistent in implementing Regional Development and Spatial Planning. Generally, local city tempted to allocate land use for housing and real estate for short term reasons.